Approach for Detection of Selfish Nodes in MANET - Varshney, Ishu; Ali, Shahjahan; Singh, Bhairvee (International Journal of Engineering and Technology, 2018)
MANET (Mobile Ad-hoc Network) is self-arranging framework using more than one mobile wireless node. The misbehaving of nodes is due to the selfish motives that appreciably decline the performance of MANET. So, itâ€™s essential to detect the selfish nodes to improve the overall potential of transmitting the data packet. Therefore, this paper basically deals with an approach on detection of selfish nodes in MANETs that further simulated in NS-2.Â Â